2011
DOI: 10.1590/s1519-69842011000400022
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of the Scalloped Hammerhead shark, Sphyrna lewini (Griffith and Smith, 1834), from the southern Brazilian coast

Abstract: Age and growth studies for the scalloped hammerhead shark, Sphyrna lewini (Griffith and Smith, 1834) caught along the southern Brazilian coast, were based on ring measurements of vertebrae sections of 115 males, 116 females and 14 unknown sexed sharks between 48 and 344 cm total length (TL). The von Bertalanffy growth models were best fit using back-calculated data. The growth parameters obtained for males, were L ∞ = 266 cm; K = 0.05/year; L 0 = 47 cm. For females, L ∞ = 300 cm; K = 0.05/year; L 0 = 51 cm. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
(25 reference statements)
4
16
0
2
Order By: Relevance
“…Accordingly, the CV value obtained in this study (6.1%) was consistent with a precise age estimation, especially since CV values as low as 6.8% (Drew et al, ) and as high as 17.9% (Harry et al, ) have been reported in studies of S. lewini elsewhere. In addition, the I APE value obtained here (4.3%) was also consistent with those obtained from previous ageing studies of S. lewini (3.2%, Piercy et al, ; 3.7%, Anislado‐Tolentino et al, ; 5.6%, Kotas et al, ), a further indication of a precise age estimation with low bias.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Accordingly, the CV value obtained in this study (6.1%) was consistent with a precise age estimation, especially since CV values as low as 6.8% (Drew et al, ) and as high as 17.9% (Harry et al, ) have been reported in studies of S. lewini elsewhere. In addition, the I APE value obtained here (4.3%) was also consistent with those obtained from previous ageing studies of S. lewini (3.2%, Piercy et al, ; 3.7%, Anislado‐Tolentino et al, ; 5.6%, Kotas et al, ), a further indication of a precise age estimation with low bias.…”
Section: Discussionsupporting
confidence: 92%
“…No significant relationship was found between peaks in 43 Ca profiles and the opaque growth bands but the peaks in 31 P:Ca and 55 Mn:Ca spatially corresponded with the annual banding pattern in most of the samples. 31 P:Ca profiles displayed 1.19 peak per opaque band while 55 Mn:Ca displayed 0.88 peak per opaque band; this closely matched the annual deposition rate in juveniles obtained from the verification analyses of this and previous studies (Branstetter, ; Harry et al, ; Kotas et al, ; Piercy et al, ). However, these interpretations remain tentative because age estimates explained only half of the variability of the elemental patterns, as shown by the low, but significant, correlation coefficients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Numerous age and growth studies have previously been undertaken on S . lewini , although none within Indonesian waters (Chen et al , ; Tolentino & Mendoza, ; de Bruyn et al , ; Piercy et al , ; Tolentino et al , ; Harry et al , ; Kotas et al , ). Few studies have been able to adequately obtain samples from all components of a population, with sex and life‐stage bias commonly occurring within S .…”
Section: Introductionmentioning
confidence: 99%